Bibliometric Analysis of Workforce Planning in the Digital Age - Loso Judijanto; Helmita Helmita (West Science Interdisciplinary Studies, 2026)
The rapid advancement of digital technologies has transformed the way organizations plan, manage, and develop their workforce. Consequently, workforce planning has become increasingly important in helping organizations adapt to digital transformation, artificial intelligence, and evolving skill requirements. This study aims to examine the intellectual structure, research trends, and emerging themes of workforce planning in the digital age through a bibliometric analysis. Bibliographic data were retrieved from the Scopus database and analyzed using VOSviewer to identify publication patterns, influential publications, keyword relationships, author collaborations, institutional networks, and country-level collaborations. The results reveal that workforce planning research is primarily concentrated around themes such as personnel management, workforce development, digital transformation, artificial intelligence, information management, and healthcare workforce systems. The keyword co-occurrence analysis indicates that personnel, workforce, digital transformation, and workforce planning are the most prominent research topics, while overlay visualization highlights recent interest in digital-age workforce management, information systems, and data-driven decision-making. Citation analysis shows that digital health and technology-enabled workforce studies have significantly influenced the field. Furthermore, collaboration analysis demonstrates strong research partnerships among authors, institutions, and countries, with Australia emerging as a major contributor to international collaboration. The findings suggest that workforce planning research is shifting toward predictive, technology-enabled, and evidence-based approaches that emphasize workforce resilience, digital competencies, and organizational adaptability. This study contributes to the literature by providing a comprehensive overview of the evolution of workforce planning research and identifying promising directions for future investigations in the context of digital transformation.